2008
DOI: 10.1007/s00125-008-0939-6
|View full text |Cite
|
Sign up to set email alerts
|

Generalised reduction of putative endothelial progenitors and CXCR4-positive peripheral blood cells in type 2 diabetes

Abstract: Aims/hypothesis In patients with type 2 diabetes, reduced levels of circulating endothelial progenitor cells have been reported and these have been correlated with disease severity. In this study, we examined a panel of markers widely used to identify progenitor and/or stem cells, and determined their association with disease severity in diabetic patients. Since expression of chemokine (C-X-C motif) receptor 4 (CXCR4) has been associated with mobilisation and recruitment of progenitor cells, CXCR4 expression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 49 publications
5
90
0
1
Order By: Relevance
“…In this issue of Diabetologia, Egan et al provide further demonstration of a reduction in EPC levels in unselected type 2 diabetic patients [4]. To understand why another confirmatory study was needed, we have to take a few steps backwards, because this hot topic has prompted broad discussion on ways of identifying and isolating the bloodderived progenitors [5].…”
mentioning
confidence: 99%
“…In this issue of Diabetologia, Egan et al provide further demonstration of a reduction in EPC levels in unselected type 2 diabetic patients [4]. To understand why another confirmatory study was needed, we have to take a few steps backwards, because this hot topic has prompted broad discussion on ways of identifying and isolating the bloodderived progenitors [5].…”
mentioning
confidence: 99%
“…The cells expressing CXCR4 correlates positively with the progenitor cells amount on normal individual, while on diabetic patients, there is no correlation. Other research indicated that there is significant decrease of CXCR4 expression in PBMC of type 2 diabetic patients [24]. The decrease of circulated EPC amount is affected by the low ability of EPC cells in responding to SDF-1 [36].…”
Section: Flow Cytometric Analysis Of Sdf-1 Relative Amountmentioning
confidence: 95%
“…Although without complication, the amount of progenitor cells majority on diabetic patients still significantly lower than healthy control. The endothelial progenitor cells reduction can also be happened on patients with high blood glucose level and HbA 1c (glycated hemoglobin) [24]. The previous research mentioned that the amount of CD34 + , one type of the immature cell which was circulated in blood and becomes the part of endothelial progenitor cells (EPC), was lower in diabetic b a a a a…”
Section: Flow Cytometric Analysis Of Cd34 + Relative Amountmentioning
confidence: 99%
“…It was reported the presence in PB of a stem cell population which lack the CD34 antigen and is able to differentiate into CD34+CD133+ EPCs, and acquire a more mature endothelial phenotype (Friedrich et al, 2006). Additionally, other populations with endothelial repair capabilities which express additional cell surface markers, including the receptor for SDF-1, the chemokine (C-X-C motif) receptor (CXCR)-4 have also been identified (Egan et al, 2008). The characterization of these different subpopulations of EPCs is due to the different methodology used for cell isolation.…”
Section: Epcs Phenotypic and Functional Propertiesmentioning
confidence: 99%
“…Additionally, several subsets of EPCs have been identified and together with other lineages of precursor cells were found to be differentially recruited to neovascular foci contributing synergistically to vasculogenic neoformation (Gulati et al, 2003;Hur et al, 2004;Lyden et al, 2001;Yoon et al, 2005a). Since their identification, an increasing body of evidence has definitely revealed the important properties and roles played by EPCs in several vascularrelated diseases, such as peripheral vascular disease (Asahara et al, 1999a(Asahara et al, , 1999bTakahashi et al, 1999), tumor neovascularisation (Asahara et al, 1999a(Asahara et al, , 1999bLyden et al, 2001) and vascular complications associated to diabetes (Goon et al, 2007;Grant et al, 2002;Egan et al, 2008;Fadini et al, 2005). The metabolic alterations present in diabetic individuals are known to profoundly affect vascular biology, being responsible for the impairment of macro-and microvascular beds (Fadini et al, 2006a;Werner et al, 2005).…”
Section: Introductionmentioning
confidence: 99%